Conocimientos y prácticas de bioseguridad del personal de salud, Unidad de Cuidados Intensivos Pediátricos Trujillo. - Urquiaga Vargas, Tania Margarita. (2021)
This is a descriptive, correlational, cross-sectional investigation, carried out in health personnel of the Pediatric Intensive Care Unit of the Regional Teaching Hospital of Trujillo, whose purpose was: to determine the relationship between the level of knowledge and biosafety practices. The sample universe was made of 20 health workers including doctors, nurses and nursing technicians; in whom the Biosafety knowledge Questionnaire and the Checklist of biosafety practices were applied. The processing of the results was developed with SPSS version 25 and they were organized in single and double entry tables, considering numerical and percentage forms. For the statistical analysis, the “Gamma statistical test” was used. Regarding the results, it was concluded as follows: The level of knowledge about biosafety in health personnel was mostly low (55 percent), medium in 40 percent and to a lesser extent high (5 percent); biosafety practices were commonly inappropriate (70 percent) and 30 percent adequate. Therefore, there is a highly significant relationship between "knowledge and practices" (p <0.01).